“I Learned More Than I Wanted”: A Phenomenological Investigation of the Experience of Having One’s Beliefs Challenged in an Undergraduate Religion Course - Steven B. Frye (Adult Education Research Conference, 2008)
This phenomenological study explored the experience of having pre-existing beliefs challenged in learning. Themes of an environment of challenge, the powerful role of the teacher, and choice stood out against the ground of the learners’ expectations of being challenged in the undergraduate religion class.
Keywords: adult learning; phenomenology; challenge; belief; religion